Wind–Wave Misalignment in Irish Waters and Its Impact on Floating Offshore Wind Turbines - Thomas Shanahan; Breiffni Fitzgerald (Energies)
This study examined the impact of wind–wave misalignment on floating offshore wind turbines (FOWTs) in Irish waters, analysing average weather and extreme events, including hurricane conditions. Using the ERA5 reanalysis dataset validated against Irish Marine Data Buoy Observation Network measurements, the results showed a satisfactory accuracy with an average wind speed error of <semantics>−0.54</semantics> m/s and a strong correlation coefficient of <semantics>0.92</semantics>. Wind–wave misalignment was found to be inversely correlated with wind speed (correlation coefficient: <semantics>−0.41</semantics>), with minimum misalignment occurring approximately seven hours after a change in wind direction. The study revealed that misalignment could exceed <semantics>30∘</semantics> during hurricanes, contradicting standard assumptions of alignment under extreme conditions. The investigation highlighted that in western coastal areas, average misalignment could reach <semantics>57.95∘</semantics>, while sheltered Irish Sea regions experienced lower values, such as <semantics>23.06∘</semantics>. Numerical simulations confirmed that these misalignment events amplified side-to-side turbine deflections significantly. This research underscores the need to incorporate misalignment effects into industry testing standards and suggests that current methodologies may underestimate fatigue loads by up to 50%. This work emphasizes improved design and testing protocols for FOWTs in complex marine environments and highlights the suitability of ERA5 for climate analysis in Ireland.